2017
DOI: 10.1016/j.otsr.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of penetration of the dorsal cortex by epiphyseal screws of distal radius volar plates: Anatomical study comparing ultrasound and fluoroscopy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…In cadaveric studies, the DTV has been found to be accurate for detecting dorsal screw penetration (Dolce et al., 2014; Giugale et al., 2017; Haug et al., 2013; Ozer et al., 2012; Riddick et al., 2012; Vernet et al., 2017). However, in small retrospective clinical series, a lower sensitivity ranging from 58% to 70% has been reported (Ganesh et al., 2016; Kiyak, 2018; Oc et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cadaveric studies, the DTV has been found to be accurate for detecting dorsal screw penetration (Dolce et al., 2014; Giugale et al., 2017; Haug et al., 2013; Ozer et al., 2012; Riddick et al., 2012; Vernet et al., 2017). However, in small retrospective clinical series, a lower sensitivity ranging from 58% to 70% has been reported (Ganesh et al., 2016; Kiyak, 2018; Oc et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The much more favourable results of the preclinical studies from Ozer et al. (2012) and Vernet et al. (2017) can be explained by the fact that the DTV was ‘perfectly pre-made’ in those studies, often using a goniometer to establish the perfect position as described by Brunner et al.…”
Section: Discussionmentioning
confidence: 99%
“…For this section only two of the method is to be focused on which is the ultrasound and radiography. Vernet et al [48] have reported that by the use of ultrasound the rate of detecting long epiphyseal screw was 43.33%. Sugun et al [50] stated the use of ultrasound has detected 59 screws that were protruding with 0.5mm or more from the dorsal cortex of distal radius from the 230 locking screw that were located at the distal rows of the locking plate.…”
Section: Assessment Of Screw-bone Implantmentioning
confidence: 99%
“…For this purpose, a medical drill is used to drill through the bone. At present, the length of the drill channel is determined manually with a caliper gauge [2]. The appropriate screw length is then selected and inserted into the bone.…”
Section: Introductionmentioning
confidence: 99%
“…The false selected screw length can then be checked by X-ray or ultrasound, but both methods have their disadvantages, e.g., exposure to radiation and extension of the operation time. Ultrasound is considered not precise enough to replace X-rays [2].…”
Section: Introductionmentioning
confidence: 99%